Early development of the ovary - Capel, Blanche (Henry Stewart Talks, 2021)
Formation of the gonad, Biopotential cell types in the fetal gonad, Commitment of the supporting cell lineage to granulosa cell fate, Germ cell cyst formation, Germ cell entry into meiosis, Cyst breakdown and primordial follicle formation, Early neuronal development in the ovary